Eksplorasi Makna Efektifitas Penggunaan AI Pada Pembelajaran Problem Solving: Perspektif Etika Siswa SMA - Nurliani Siregar; Ribka Aprilia Pakpahan; Yuni Ambarita; Kristin Asra Panjaitan; Nisa Windy Siagian (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study explores the significance of the effectiveness of AI use in problem-solving learning: an ethical perspective from high school students. This study uses a qualitative approach and interviews with a descriptive exploratory method. This research aims to understand and describe in depth the significance of the effectiveness of using artificial intelligence (AI) in problem-solving learning from the ethical perspective of high school students. Overall, the effectiveness and ethics of AI use are two interrelated aspects. AI can only have a truly positive impact if accompanied by moral control and critical awareness. Without ethics, AI can lead to academic misinformation and misinformation. With strong ethics, students will not only become skilled AI users but also responsible and able to utilize AI as an accurate, safe, and reliable learning resource. The integration of AI in secondary education, therefore, is successful if these two aspects are balanced.